Hidden Curriculum Strategy in the Formation of Tolerance: A Case Study at Tebuireng Islamic Boarding School - Ishomuddin, Mukhammad; Aziz , Abdullah Aminuddin (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze hidden curriculum strategies in fostering tolerance attitudes at Tebuireng Islamic Boarding School as a replicable model of tolerance education. Using a descriptive qualitative approach with a case study method, the research was conducted over six months, involving the deputy head of the boarding school, the academic council, the coordinator of mentors, mentors, and students as research subjects. The findings reveal that the hidden curriculum operates through three dimensions: structural via the Student-friendly Islamic boarding school program, interactional through dialogic communication between mentors and students, and cultural via institutional openness and diversification of extracurricular activities. Implementation follows a systematic pattern from the micro level (room) through amar ma'ruf nahi munkar, the meso level (boarding school) with social activities, to the macro level (community) through interfaith dialogue. Students active in extracurricular activities have higher tolerance levels. This study produces the Tri-Dimensional Hidden Curriculum concept, which integrates Jackson's theory with boarding school values, contributing theoretically and practically to the development of tolerant character education in Indonesia.